Regional Gender Action Plan for the Middle East and North Africa Region, FY13-FY16 - World Bank (Washington, DC, 2013)
The Middle East and North Africa (MENA) region is experiencing a time of momentous change. Some countries are in the midst of a profound political, economic, and demographic transition, others are striving to emerge from protracted conflict, yet others are experiencing internal tensions and rising demands for more citizen voice. This period of change and uncertainty presents challenges and opportunities, including with regard to gender issues. Yet some governments may not prioritize gender issues, while in others there could be a regression. MENA Regional Gender Action Plan (RGAP) is part of the World Bank's institutional commitment to operationalize the policy priorities identified in the WDR 2012 and the regional companion to the World Development Report (WDR) 2012. The MENA Regional Gender Action Plan (RGAP) will require that the Bank be nimble and practical in its approach to advancing gender equality in the region. The MENA RGAP provides a two-pronged approach to supporting MENA countries in advancing gender equality: Prong 1: through country programs; and Prong 2: championing dialogue.